Numerical and Geometrical Evaluation of Steel Plates with Transverse Hat-Stiffeners Under Bending - Mariana Alvarenga Alves; Eduarda Machado Rodrigues; Luiz Alberto Oliveira Rocha; Elizaldo Domingues dos Santos; William Ramires Almeida; Liércio André Isoldi (Metals)
Thin steel plates with stiffeners are widely used in shipbuilding, aeronautics, and civil construction due to their lightness and structural strength. This study presents a numerical model developed using ANSYS Mechanical APDL with SHELL281 finite elements to evaluate the deflection of thin steel plates with trapezoidal-shaped box-beam stiffeners, known as hat-stiffened plates. The structure is analyzed under a uniformly distributed load perpendicular to the plate, with simply supported boundary conditions. The constructal design method combined with the exhaustive search technique is employed to optimize the geometry. A volume fraction of 30% is used, transferring material from the reference plate (without stiffeners) to the stiffeners, defining parameters such as number, height, and thickness—considered degrees of freedom. The stiffener angle is fixed at 120°. The results show that increasing stiffener height and reducing thickness generally improve structural performance by reducing deflections. The best configuration with transverse stiffeners reduced deflection by 97.15% compared to the reference plate, and by 79.27% compared to the best longitudinal configuration from previous studies. Therefore, transverse stiffeners were more effective than longitudinal ones. This study highlights the importance of stiffener orientation and geometry in the structural optimization of thin steel plates.